Analysis of the German DRG data for livedoid vasculopathy and calciphylaxis. (29th March 2017) - Renner, R.; Dissemond, J.; Goerge, T.; Hoff, N.; Kröger, K.; Erfurt‐Berge, C.
Abstract: Background: Livedoid vasculopathy and calciphylaxis are rare skin disorders. Large cohorts of patients have been missing so far for detailed analysis. Patients and methods: Data from diagnosis‐related groups (DRGs) of hospitalized cases of livedoid vasculopathy ( n total = 1357) and calciphylaxis ( n total = 699) were analysed for the years 2008‐2013 concerning sex, age and frequency of diagnosis. To avoid deviations to non‐relevant secondary diagnosis and due to changes in ICD‐10 indices, we selected the two most recent available years 2013 and 2014 for evaluation of the accompanying diagnoses for both, livedoid vasculopathy ( n = 519) and calciphylaxis ( n = 324). Those were additionally evaluated as possible comorbidity. Results: The male–female ratio for livedoid vasculopathy was 2.1:1. Patients older than 45 years comprehended 74.7% of all patients with peaks between the ages of 45–50 and 70–75. Livedoid vasculopathy patients suffered from cardiovascular and renal diseases. Coding of coagulation disorders was found rarely in our analysis. For calciphylaxis, we calculated a male–female ratio of 1.7:1. Most of the patients were at an age between 65 and 80 years. Diagnosis at an age under 35 years was rare. In general, most calciphylaxis patients showed end‐stage renal disease with need of dialysis and presented with the resulting complications. Conclusions: Our data analysis shows relevant comorbidity and cofactors of these rare diseases like livedoid vasculopathy and calciphylaxis in Germany by a large number of cases.